2015
DOI: 10.1097/01.pra.0000460620.87557.02
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Identification in Psychiatric Disorders

Abstract: Patients with psychiatric disorders exhibit several neurobehavioral and neuropsychological alterations compared to healthy controls. However, signature endpoints of these behavioral manifestations have not yet been translated into clinical tests for diagnosis and follow-up measures. Recently, neuroproteomic approaches have been utilized to identify unique signature markers indicative of these disorders. Development of reliable biomarkers has the potential to revolutionize the diagnosis, classification, and mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Substantial efforts have been aimed at the identification of biomarkers in schizophrenia. Genetic, neurophysiological, neuroimaging and neurochemical studies aim to identify a specific biological marker for schizophrenia (5). In clinical practice, the investigation of a biomarker in the blood may be considered the best way to support the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial efforts have been aimed at the identification of biomarkers in schizophrenia. Genetic, neurophysiological, neuroimaging and neurochemical studies aim to identify a specific biological marker for schizophrenia (5). In clinical practice, the investigation of a biomarker in the blood may be considered the best way to support the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in the literature have investigated potential biomarkers of schizophrenia. However, no biomarker that is pathognomonic for schizophrenia has been identified (5). The d -amino acid oxidase (DAAO) and G72 genes have recently gained attention because of their association with schizophrenia, as well as their potential role in glutamatergic neurotransmission (6).…”
Section: Introductionmentioning
confidence: 99%
“…In the search for possible imaging biomarkers of aggression, a reduced gray matter volume at the level of the orbitofrontal cortex and low amygdala volume have both been linked with predisposition to violence ( Matthies et al, 2012 ; Pardini et al, 2014 ; Bannon et al, 2015 ). Collectively, although brain imaging studies have revealed important information about the neuroanatomy underlying aggressive and impulsive behavior, this knowledge cannot yet be used to predict aggression in humans ( Razafsha et al, 2015 ). In the future, imaging studies in patients with epilepsy in whom aggression develops or worsens after AED treatment may help identify brain abnormalities associated with epilepsy and aggression and may identify prognostic markers of aggression in patients with epilepsy.…”
Section: Neurobiology and Psychopharmacology Of Epilepsy And Aggrmentioning
confidence: 99%
“…Current diagnosis of schizophrenia is based on observed behaviors and psychiatric symptoms [ 12 ]. However, in many cases, psychiatrists are divided on the diagnosis of schizophrenia due to lack of quantitative measures such as biomarkers [ 13 ]. Therefore, it is of clinical importance to find biomarkers to diagnose schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of clinical importance to find biomarkers to diagnose schizophrenia. Machine learning based on MRI measures, or the so-called multivariate pattern analysis technique, provides a promising way to find biomarkers for schizophrenia classification [ 12 , 13 , 14 ]. Xiao et al created a support vector machine (SVM) model which could classify schizophrenia patients and normal subjects based on whole brain gray matter densities from sMRI [ 15 ].…”
Section: Introductionmentioning
confidence: 99%